Suppression Distortion Product Otoacoustic Emission (Suppression DPOAE) using Various Contralateral Suppressors among Autism Spectrum Disorder Children - Jamal, Fatin Nabilah; Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Rahmat, Sarah; Ahmad Basri, Nadzirah; Sidek, Shahrul Na'im; Md. Yusof, Hazlina; Khalid, Madihah (2021)
Background: Auditory sensory gating deficits is an abnormality in Autism Spectrum Disorder (ASD) patient that leads to sensory processing difficulty. It is particularly difficult for ASD children to discriminate multiple auditory stimuli, which hinders them to focus on one auditory stimulus and separating unnecessary sounds. Suppression DPOAE is a tool used to identify sensory gating deficit in the general population and specifically in ASD children. This paper aims to investigate the suppression effect among ASD children using various types of sounds suppressors in order to address the inability of ASD children in filtering unnecessary information. Methods: A total of 20 children with 10 ASD children and 10 normal developing children aged 6-12 years old will be recruited. The DPOAE is elicited from one accessible ear by presenting two pure tones frequencies (with an f2/f1 ratio of 1.22) at 1kHz, 2kHz, 4kHz, 6kHz. and 8kHz. Meanwhile, suppressor sounds will be presented on another ear. Several types of sounds have been chosen as contralateral suppressor including white noise, environmental sounds, natural sounds, Quranic recitation, and piano sounds. The amount of DPOAE suppression will be determined by identifying the difference between DPOAE amplitude baselines without masker and with the presentation of masker in dB sound pressure level for all sound types. Results: Sound with the highest suppression effect was determined using effect size calculation and RM ANOVA. A high suppression effect may suggest high sensory gating performance while low suppression may indicate low sensory gating performance. Conclusion: This study provides a better understanding of the alternative sound stimuli to assess sensory gating deficit among ASD children besides the standard white noise tone. Sound with a high suppression effect has the potential to be used for sound therapy intervention among ASD children as part of rehabilitation and therapy.